A Wearable Wisdom: ABI-Modal Behavioral Biometric Scheme for Smartwatch User Authentication - Bandaru Chennakesava Naidu; Allam Rakesh; Maridi Banda Eswar; Nagiri Ganesh Naidu; Mrs. Rohini (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This work utilizes wearable devices for real-time stress detection and investigates the effectiveness of meditation audio in reducing stress levels after academic exposure. Physiological data, including Interbeat Interval (IBI)-derived Heart Rate Variability (HRV), Blood Volume Pulse(BVP),andelectrodermalactivity(EDA),arecollectedduringthe Montreal Imaging Stress Task (MIST). The stress classification methodology employs an integrated approach using Genetic Algorithm andMutualInformationtoreducefeaturesetredundancy.Itfurtheruses Bayesian optimization to fine-tune machine learning hyperparameters. The results indicate that the combination of EDA, BVP, and HRV achievesthehighestclassificationaccuracyof98.28%and97.02%using the Gradient Boosting (GB) algorithm for 2-level and 3-level stress classification. In contrast, EDA and HRV alone achieve a comparable accuracy of 97.07% and 95.23% for 2-level and 3-level stress classification, respectively. Furthermore, the SHAP Explainable AI (XAI) analysis confirms that HRV and EDA are the most significant features for stress classification. The study also finds evidence that listening to meditation audio reduces stress levels. These findings highlight the potential of wearable technology combined with machine learning for real-time stress monitoring and management in academic environments.